Management and utilization of the Fund for Innovative Medicines: a multistakeholder qualitative survey on regional and local practices - Andrea Vitagliano; Marzia Bonfanti; Chiara Lucchetti; Andrea Marcellusi (Global & Regional Health Technology Assessment)
Introduction: The Fund for Innovative Medicines, Fondo Farmaci Innovativi (FFI), enables financing, non-competition, and fast access to innovative medicines. However, limited evidence exists regarding its management processes and the stakeholders involved. In order to identify characteristics, critical issues, and improvement opportunities, this analysis investigates the FFI management processes through the perspective of the Key Opinion Leaders (KOLs) involved.